The Role of Yaumul-Fannil-Lughawi in Promoting Multilingual Practices at Mahad Al Jamiah - Moh Nawalul Fawaid El Haqi; Ribut Wahyudi (Universitas Pendidikan Mandalika, 2026)
The difficulty of bilingual practice at one of the Islamic Boarding Colleges (Mahad Al Jamiah) institutions in East Java is a clear indication of the mahasantri’s (students’) lack of confidence. The language policy known as “yaumul-fannil-lughawi” provides mahasantri with the chance to practice bilingualism in the Mahad environment. They have different perspectives and ways of thinking, and mahasantri can respond differently. These conditions cause resistance among the mahasantri in Mahad towards implementing multilingual practices. As such, it is imperative to scrutinize the language policy practices in Mahad, specifically, the conclusions and answers about positive, neutral, and negative language practices. According to this study, other factors have also contributed to the successful improvement of Mahad’s language environment, in addition to the implementation of yaumul-fannil-lughawi (language policy). There are still many mahasantri who lack confidence in their language skills. The fact that some mahasantri hide in the toilet as a means of protest shows that the (language policy) has not succeeded in ensuring that every mahasantri is satisfied. Hence, the multilingual practice in Mahad demonstrates that the bilingual language policy is not being correctly implemented, despite it being in place. There needs to be mature collaboration in designing a language program.